The United States dominates global investment banking: Does it matter for Europe? - Charles Goodhart; Dirk Schoenmaker (Bruegel, 2016)
[Highlights] For the full references and the annex, please see the PDF version of this publication. In the aftermath of the global financial crisis, the market share of US investment banks is increasing, while that of their European counterparts is declining. We present evidence that US investment banks are on the verge of taking over pole position in European investment banking. Meanwhile, since 2015, Chinese investment banks have overtaken American and European investment banks in the Asia-Pacific market. Credit rating agencies and investment banks are the gatekeepers of the capital markets. The European supervisory institutions can effectively supervise the European operations of these US-managed players. On the political side, we suggest that the European Commission should continue to view its, albeit declining, banking industry as a strategic sector. The Commission, the European Central Bank and the Bank of England should jointly develop a strategic agenda for the EU-US Regulatory Dialogue. Finally, corporates rely on investment banks to issue new securities. We recommend that the big European corporates should cherish the (few) remaining European investment banks, by giving them at least one place in otherwise US- dominated banking syndicates. That could help to avoid complete dependence on US investment banks.
Keywords: 330